Function of chromatin structure and dynamics in DNA damage, repair and misrepair: γ-rays and protons in action - Ježková, Lucie; Falk, Martin; Falková, Iva; Davídková, Marie; Bačíková, Alena; Štefančíková, Lenka; Vachelová, Jana; Michaelidesová, Anna; Lukášová, Emilie; Boreyko, Alla; Krasavin, Evgeny; Kozubek, Stanislav (Applied radiation and isotopes, 2014)
According to their physical characteristics, protons and ion beams promise a revolution in cancer radiotherapy. Curing protocols however reflect rather the empirical knowledge than experimental data on DNA repair. This especially holds for the spatio-temporal organization of repair processes in the context of higher-order chromatin structure-the problematics addressed in this work. The consequences for the mechanism of chromosomal translocations are compared for gamma rays and proton beams.
Keywords: Humans; Protons; translokace genetická; Cell Nucleus; Gamma Rays; Higher-order chromatin structure and DSB repair; mikroskopie; Gamma rays and proton beams; oprava DNA; protony; Formation of chromosomal translocations; Translocation, Genetic; záření gama; buněčné jádro; chromatin; lidé; DNA double-strand breaks (DSBs); Cells, Cultured; Chromatin; DNA Repair; γH2AX foci; kultivované buňky; poškození DNA; DNA Damage; Microscopy